Модели операций интеграции функциональных сервисов в информационной системе управления предприятием - Евланов, М. В.; Васильцова, Н. В.; Никитюк, В. А. (НТУ "ХПИ", 2014)
Проведен анализ основных направлений развития сервис-ориентированных информационных систем. Разработаны математические модели операций интеграции описаний отдельных функциональных сервисов в реестр актуальных сервисов информационной системы. Предложен унифицированный метод интеграции отдельных функциональных сервисов, основным преимуществом которого является возможность досрочного прекращения выполнения операции интеграции, если обнаруживается ошибка, вызванная несоответствием описаний сервиса описаниям предметной области.

The analysis of the major trends in the development of service-oriented information systems. The mathematical models of operations integration of individual functional descriptions of services in the register of current services information system are developed. Authors determined the conditions of operations integration services. The features of these operations for different units of service registry. The proposed model operations allow us to consider the implementation of these operations by querying the database, implementing a service registry, in one of the standard data manipulation language. The unified method of integration of individual functional services is used.
Model of operations of integration of functional servicesin information system of enterprise management
Keywords: сервис-ориентированная архитектура; интеграция; реестр; онтология; information system; service-oriented architecture; functional service; integration; registry; ontology